Overcoming Resistance and Fostering Adaptation: Change Management Strategies at BPJS Kesehatan - Muhammad Zamzami; Damar Lia Susanti; Retno Jiwo Utami; Nur Qurotul Ayuni (Journal Informatic, Education and Management (JIEM), 2026)
The organizational transformation undertaken by BPJS Kesehatan in responding to the dynamics of public service delivery, digitalization, and increasing participant expectations is often hindered by the emergence of internal resistance. This resistance manifests in various forms, including limited understanding of the urgency of change, concerns regarding its impact on job roles, inadequate digital competencies, and a bureaucratic culture that does not fully support innovation. This study aims to identify the patterns and factors driving resistance to change within BPJS Kesehatan and to formulate effective and sustainable change management strategies. Based on literature analysis and empirical findings, resistance is primarily influenced by suboptimal internal communication (68%), insufficient understanding of the direction of change (70%), and anxiety about its impact on work responsibilities (65%). Through strategic analysis, this research emphasizes the importance of transparent and participatory communication, competency enhancement through adaptive training, application of the ADKAR model, strengthening an innovative organizational culture, and implementing data-driven monitoring and feedback mechanisms. The findings demonstrate that a people-centered approach to change management can reduce resistance, increase employee engagement, and reinforce the organization's adaptive capacity. With consistent implementation, these strategies have the potential to enhance the effectiveness of BPJS Kesehatan’s transformation efforts and sustainably improve public service quality.